AL- ṬAḤĀWĪ’S METHOD TOWARDS THE VARIETY OF QIRAĀT IN TAFSIR AḤKĀM AL-QUR’ĀN AND ITS IMPLICATION TO ISTINBĀṬ AL-AḤKĀM - Moh Abdul Kholiq Hasan (UIN Sunan Kalijaga Yogyakarta, 2021)
The variety of Qiraāt is closely related to the interpretation of the Quran. Often, variety of Qiraāt result in different understanding and law. Al-Tahāwī gives special attention on the variety of Qiraāt and its use in the istinbāṭ of fiqh rulings in his interpretation entitled Ahkām al-Qur'ān al-Karīm. This research aims at investigating al-Tahāwī’s method towards the variety of Qiraāt and its implication in the istinbāṭ of fiqh rulings. This research paper employs analytic descriptive method by exploring and analyzing the variety of Qiraāt included in the interpretation entitled Ahkām al-Qur’ān al-Karīm. The results showed that al-Tahāwī's interaction methods towards the variety of Qiraāt are: (1) providing all possible Qiraāt; (2) verifying the validity of Qiraāt; (3) explaining Qiraāt Syāżah. This method is very influential in the istinbāṭ of fiqh rulings because al-Tahāwī’s orientation on presenting variety of Qiraāt is related to the istinbāṭ of fiqh rulings itself. al-Tahāwī tried to compromise the variety of Qiraāt and confirmed his choices, far from being mażhab fanatics as those found in al-Jaṣāṣ, Ilkiyā al-Harāsi and Ibn al-‘Arabi.Keywords: Ahkām al-Qur’ān al-Karīm, al-Tahāwī, the variety of Qur’an recitations, Fiqh rulings. ",